(3Gdabg GdfGaY aj aQhY GdMfajIs - (3fGUQ GdOjf CHh GdbGSe eMeO Hf jhSa GdMSfj GdeOfj GdSeQbfOj GdMfaj,J (B656 (3g` s ((3jYbhH Hf TjNs)
(3ChdgG (B:s
(3GdMeO ddg MeOkG CeOg GdCHO cJGH GdWgGQGJ s
(3BNQgG (B:s
( (3cJGH GdNfKi (B) (3aUGQ dg NeSg ef EKfi YTQ SgekG , hddCHf SHYI ef EKfi YTQ JeJ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdCHhGH hGdcJH HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3Gdabg GdMfajs